Augmenting Expert Elicitation with Structured Visual Deliberation. Issue 3 (18th July 2016) - van Gelder, Timothy; Vodicka, Roger; Armstrong, Nicholas
Abstract: Policy decisions frequently depend on quantitative judgements made by domain experts. The quality of those judgements depends in turn on the nature of the procedures used to obtain them. Procedures designed for this task are known as expert elicitation. This article explores how expert elicitation can be enhanced by supporting the deliberations of expert groups with diagrammatic methods for displaying the structure of those deliberations. It describes an elicitation exercise in which a team from the Defence Science and Technology Group estimated rates of loss of an aircraft that might be acquired for the Australian Defence Force. A structured visual deliberation method, dialogue mapping, was used to facilitate the discussions of the panel of experts in between two rounds of estimations in a Delphi‐type elicitation process. The enhanced elicitation approach worked well for the attrition estimation project, and a similar approach may be useful in many other contexts.